Examining the dimensionality of pre-service teachers’ enthusiasm for teaching by combining frameworks of educational science and organizational psychology - Bock, Denise; Harms, Ute; Mahler, Daniela (PloS one, 2021)
The aim of this study was to obtain a holistic understanding of pre-service teachers’ enthusiasm for teaching (a subject) by examining its structure as well as relevant factors that may be related to it in the first phase of teacher education. For this purpose, we considered two strands of research: educational science and organizational psychology. Accordingly, the professional competence model and the job demands and resources model helped to identify factors that are associated with pre-service teachers’ enthusiasm for teaching. Responses of 211 pre-service biology teachers indicated that enthusiasm for teaching can be considered as one-dimensional. Moreover, we found positive relationships between enthusiasm for teaching and academic self-concept, intrinsic career choice motives and occupational commitment. In contrast, we detected negative relations between enthusiasm for teaching and both emotional exhaustion and intention to quit. No significant relations could be found for enthusiasm for teaching and both professional knowledge and extrinsic career choice motives. Our findings highlight the importance of enthusiasm for teaching in the earliest stage of teachers’ careers. Thus, our study points out relevant factors that could help to maintain high enthusiasm and to keep (pre-service) teachers healthy and in the profession.